Evaluation of undergraduate forensic medicine education in Nepal: a critical analysis using Schwab’s five commonplaces and Schubert’s curriculum images - Alok Atreya; Roshani Rajbanshi; Ritesh G. Menezes; Apurba Acharya (BMC Medical Education)
Abstract Following the establishment of Nepal’s first medical college in 1972, forensic medicine was introduced in 1978. To date, 25 medical colleges in the country have included forensic medicine as a compulsory subject in the undergraduate medical curriculum. Although this subject has been introduced into the medical curriculum, the outcome is unsatisfactory, as reflected by the poor medico-legal reports prepared by newly graduated medical students. Forensic medicine education is therefore at a critical juncture with challenges while paving the way for opportunities to improve. In this analysis, we examined the current state of forensic medicine education for the undergraduate medical programme in the country. For this purpose, we used Schwab’s five commonplaces in the curriculum. We then evaluated the curriculum from the perspective of Schubert’s curricular image frameworks. We noted significant differences in the curriculum content, teaching methods, and practical training across the curriculum. An acute shortage of qualified teachers, limited resources, and inconsistent curriculum updates have further complicated the situation. The current curriculum does not address cultural sensitivity, which should not be overlooked during medico-legal practices. Following the curriculum evaluation, we find room for improvement and propose recommendations. First, the forensic medicine curriculum should be standardized and uniform to address national needs. There should be uniformity and improvement in practical hands-on training. The manpower should be trained to work in rural settings with limited resources so that the overall justice system of the country can improve. Recent technological advances should be incorporated into the curriculum and interdisciplinary collaboration encouraged. Allocating more scholarship/sponsorship seats for postgraduate programmes and recruiting skilled graduates to be evenly distributed regionally would be important steps toward strengthening the country’s medico-legal proceedings and justice system.